P-star model approach of linking money and price in Thailand - Maggie,, Tang May Jean. (Universiti Malaysia Sarawak (UNIMAS), 2009)
Simple sum monetary aggregate is the traditional monetary aggregate that is used by central banks in the world in monetary policy. The relationship between simple sum monetary aggrega te and inflation had been proven by many past studies. However, the increasing of financial liberalization in 1980s has blurred the relationship bet ween money and price. M any alternative monetary aggregates have been introduced. One of them is Divisia monetary aggregate. This study compares the perform ance of s imple sum and Divisia monetary aggregate s in Thailand by using P - Star model . Using quarterl y data from 1993:1 to 2005:4, the result in this study illust rated that simple sum M2 contains more information in predicting inflationary movement in Thailand compared to other monetary aggregate s . In addition, P - Star model can perform well in tracking in flation in Thailand.